Adult-Onset Still's Disease Masquerading as Sepsis in an Asplenic Active Duty Soldier. (25th November 2012) - Jaqua, Nathan T.; Finger, David; Hawley, Joshua S.
Abstract : This is a case of a 26-year-old active duty male with a history of idiopathic thrombocytopenic purpura (ITP) and surgical asplenia who presented with a one-week history of fevers, myalgias, arthralgias, and rigors. His evaluation upon presentation was significant for a temperature of 103 degrees F, white blood cell count of 36 K with a granulocytic predominance, and elevated transaminases. He was treated empirically with broad-spectrum antibiotics with concern for a systemic infection with an encapsulated organism. During his stay, he developed four SIRS criteria and was transferred to the progressive care unit for suspected sepsis. He continued to have twice-daily fevers and a faint, salmon-colored centripetal rash was eventually observed during his febrile episodes. After a nondiagnostic microbiologic and serologic workup, he was diagnosed with adult-onset Still's Disease and started on intravenous methylprednisolone with brisk response. He was discharged on oral prednisone and was started on anakinra. Adult-onset Still's disease is a rare condition that presents with varying severity, and this is the first reported case, to our knowledge, of its diagnosis in an asplenic patient. Its management in the setting of asplenia is complicated by the need for antibiotic therapy with each episode of fever.